Islamic Justice in Indonesia Polygamy Regulation on Asghar Ali Engineer’s Perspective - Mayasari, Lutfiana Dwi; Cahya, Akmal Adi; Agustina, Ulfa Wulan (UIN Sunan Kalijaga Yogyakarta, 2021)
Indonesia has formulated the regulation of polygamy. Those regulations did not provide a contextual justice, especially towards women, at least if it viewed from some perspective. This research tries to measure the justice on those regulations on Asghar Ali engineer’s perspective of justice. This article is library research which use a normative and qualitative approach along with triangulation as collecting data method. Based on this article discussion, we find a conclusion that Indonesia provides the women/wife a chance to participate in the session process. Indonesia arranged that the wife’s agreement is one of requirement for husband to demand polygamy before the court. Therefore, in the view of Asghar, marriage law of Indonesia respect towards women if it regulation obeyed by the judge. In his view, justice for weak-side is the basis and fundamental teachings of Islam. The justice referred to him, is substantive justice, not just justice in the text.